Detection of anti-infliximab antibodies is impacted by antibody titer, infliximab level and IgG4 antibodies: a systematic comparison of three different assays - Afonso, Joana (2016)
Background: There is scant information on the accuracy of different assays used to measure anti-infliximab antibodies (ADAs), especially in the presence of detectable infliximab (IFX). We thus aimed to evaluate and compare three different assays for the detection of IFX and ADAs and to clarify the impact of the presence of circulating IFX on the accuracy of the ADA assays.Methods: Blood samples from 79 ulcerative colitis (UC) patients treated with infliximab were assessed for IFX levels and ADAs using three different assays: an in-house assay and two commercial kits, Immundiagnostik and Theradiag. Sera samples with ADAs and undetectable levels of IFX were spiked with exogenous IFX and analyzed for ADAs.Results: The three assays showed 81-96% agreement for the measured IFX level. However, the in-house assay and Immundiagnostik assays detected ADAs in 34 out of 79 samples, whereas Theradiag only detected ADAs in 24 samples. Samples negative for ADAs with Theradiag, but ADA-positive in both the in-house and Immundiagnostik assays, were positive for IFX or IgG4 ADAs. In spiking experiments, a low concentration of exogenous IFX (5 mu g/ml) hampered ADA detection with Theradiag in sera samples with ADA levels of between 3 and 10 mu g/ml. In the Immundiagnostik assay detection interference was only observed at concentrations of exogenous IFX higher than 30 mu g/ml. However, in samples with high levels of ADAs (> 25 mu g/ml) interference was only observed at IFX concentrations higher than 100 mu g/ml in all three assays. Binary (IFX/ADA) stratification of the results showed that IFX+/ADA and IFX-/ADAs + were less influenced by the assay results than the double-positive (IFX+/ADAs+) and double-negative (IFX-/ADAs-) combination.Conclusions: All three methodologies are equally suitable for measuring IFX levels. However, erroneous therapeutic decisions may occur when patients show double-negative (IFX-/ADAs) or double-positive (IFX+/ADAs+) status, since agreement between assays is significantly lower in these circumstances.